(untitled) (Al-Farooq Journal of Sciences, 2026)
This study was conducted to investigate the effect of neem (Azadirachta indica) seed and leaf oil extract on larvae and adults of Anopheles stephensi mosquitoes in the Biology Laboratory, Faculty of Education (Bayda), Omar Al-Mukhtar University, Libya. The Anopheles mosquito larvae 3rd larval instar was obtained from laboratory colony established in the insectary. Larvae were maintained at a temperature of 25± 1°C, with a relative humidity of 80± 5%, and a photoperiod of 12/ 12 hours light/ dark. For the larvicidal bioassay, six concentrations (50, 100, 150, 200, 250 and 300 ml/l) of seed oil and leaf extract of A. indica. A set of the control group using distilled water was included. The 100 % larval mortality was observed due to both A. indica seed oil and extract at concentration of 300 ml/l followed by 250 ml/l after exposure to 72 hours while the control treatment don’t recorder any adults mortality percentage under treatment with neem oil and neem leaf extracts against Anopheles stephensi larvae. The results show that the mortality rate of Anopheles stephensi larvae increases with increasing concentration of both neem oil extract and neem leaf extract with increasing exposure period. The extracts of neem leaves of Azadirachta indica demonstrated strong larvicidal activity, with LC50 and LC90 values, with neem oil and neem leaf extracts.